Editorial: Towards a psychophysiological approach in physical activity, exercise, and sports, volume II - Forte, Pedro (2024)
In recent years, there has been an increase in interest in mental health disorders as a result of mediatic coverage of Olympic athletes’ mental health struggles, and also due to the COVID-19 pandemic lockdowns. These phenomena helped to further exacerbate a problem already extensively present in sport and society. Therefore, applying a psychophysiological approach to physical activity, exercise, and sports research has become very popular. Indeed, mental fatigue and mental disorders are not only psychological in origin, but also require an explanation from a psychophysiological perspective due to the effective interconnection between the psychological and physiological dimensions. Psychological variables can also influence performance and the psychophysiological system has a strong effect on the control of physical capacities. Moreover, pacing behaviour, decision-making, self-regulation, and effort perception can also explain the role of the brain in physical activity and exercise management. Thus, the aim of this Research Topic is to share the impact of a psychophysiological approach in physical activity, exercise, and sports. The goal of this Topic is to address the following: • Factors determining performance, including technical/tactical, physiological, cognitive, and psychosocial; • training and competition demand; • training interventions and testing in sports; • acute and chronic effects of training in psychophysiological variables; • coaching in sports; • strength and conditioning, mental health, and performance; • recent developments within sports sciences research. This Research Topic endeavors to explore at specific themes related to physiological stress and mental well-being. Additionally, we aim to provide evidence to coaches and sports scientists highlighting the relationship between training and competition demands, related to performance. We also want to analyze the effects of strength and conditioning training, and coaching effects (acute and chronic) on psychological and physiological. Finally, it is our intention to provide scientific literature with evidence for a relationship between movement, behavior and cognition with physiological performance: the psychophysiological approach.